Suppurative thyroiditis: Systematic review and clinical guidance. (2nd March 2021) - Lafontaine, Nicole; Learoyd, Diana; Farrell, Stephen; Wong, Rosemary
Abstract: Objective: Acute suppurative thyroiditis (AST) is a rare but potentially fatal condition which can initially be difficult to distinguish from the more common subacute thyroiditis (SAT). We aim to update understanding of this medical emergency. Design: A systematic review over the past 20 years was performed on the epidemiology, clinical features, investigations, management and outcomes of AST. All full‐text cases of microscopy or culture‐ proven AST in the English literature were included. Results: 200 cases of AST have been described in 148 articles from January 2000 – January 2020. Bacterial AST is most common, often presenting with neck pain (89%) and fever (82%). Immunosuppression and pyriform sinus fistula are the most common causes, most often due to gram‐positive aerobes. Transient hyperthyroidism is common (42%). Aspiration and antibiotics are becoming a more common treatment. Overall mortality was 7.8%. Tuberculous and fungal AST are less likely to present with fever and neck pain. Fungal AST is more common in immunosuppressed individuals (31%) and has a high overall mortality (33%). Tuberculous AST is more common in TB endemic areas. Conclusion: The symptoms and signs of AST commonly overlap with SAT and initially can be hard to diagnose. AST can be rapidly morbid or even fatal. Clinicians need to consider AST when they assess patients with thyroiditis who are systemically unwell, have high fever, high white cell count and c‐reactive protein, tender neck and abnormal neck imaging. An investigative and treatment strategy is described based on a systematic review of the literature.